1999
DOI: 10.1038/10712
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: T cell activation through the CD2 cell surface receptor is transmitted by proline-rich sequences within its cytoplasmic tail. A membrane-proximal proline-rich tandem repeat, involved in cytokine production, is recognized by the intracellular CD2 binding protein CD2BP2. We solved the solution structure of the CD2 binding domain of CD2BP2, which we name the glycine-tyrosine-phenylalanine (GYF) domain. The GYF sequence is part of a structurally unique bulge-helix-bulge motif that constitutes the major binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 37 publications
1
40
0
4
Order By: Relevance
“…In an earlier report on the CD2BP2 protein, partial human sequences corresponding to GIGYF1 and GIGYF2 were recognized in GenBank TM (36). Using the complete mouse cDNAs that we have cloned, analysis of the human genome sequence and available DNA sequences from multiple other species indicate that GIGYF1 and GIGYF2 are the only two members of this protein family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier report on the CD2BP2 protein, partial human sequences corresponding to GIGYF1 and GIGYF2 were recognized in GenBank TM (36). Using the complete mouse cDNAs that we have cloned, analysis of the human genome sequence and available DNA sequences from multiple other species indicate that GIGYF1 and GIGYF2 are the only two members of this protein family.…”
Section: Discussionmentioning
confidence: 99%
“…The 17-aa GYF domain was described initially as a proline-rich interactive motif in CD2BP2 (37), and, based on crystal structure data, it has been proposed that a bulge-helix-bulge conformation of the GYF domain interacts with paired proline-rich sequences (36). Using mutant constructs of GIGYF1, we have shown that its interaction with Grb10 in two-hybrid assays exhibits sequence requirements similar to those essential for the binding of the CD2BP2 GYF domain to CD2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD2BP2 contains a C-terminal fragment of ϳ60 amino acids that confers binding to these proline-rich sequences. Structurally, this so-called GYF domain represents a small ␣/␤ protein that displays a set of aromatic residues from a unique bulge-helix-bulge motif creating a hydrophobic pocket accommodating the PPG core of the binding peptide (1,4,5). In addition to this core sequence, the positively charged arginine residues in the vicinity of the PPG motif contribute to binding of the CD2 and SmB/BЈ ligand.…”
mentioning
confidence: 99%
“…Subsequently, a nuclear role for CD2BP2 was suggested, based on reports that identified CD2BP2 as a protein associated with spliceosomal complexes and proteins involved in splicing (2, 3). CD2 and SmB/BЈ share the presence of (R/K/G)XXP-PGX(R/K) motifs that were shown to bind to CD2BP2 in vitro and in vivo (1,3,4). CD2BP2 contains a C-terminal fragment of ϳ60 amino acids that confers binding to these proline-rich sequences.…”
mentioning
confidence: 99%